Advancing Therapeutic Horizons: Niosomal Transdermal Drug Delivery for the Management of Lumpy Skin Disease - Kumar, K.L. Senthil; Sindhu , E.; Vasanthan, A. (Asian Journal of Pharmaceutical Research and Development, 2024)
Lumpy skin disease (LSD) poses a significant threat to the global cattle population, impacting both animal welfare and economic stability in affected regions. Despite various control measures, the disease continues to challenge veterinary professionals. Hypothesis: Exploring the Potential of Niosomal Transdermal Drug Delivery for the Management of Lumpy Skin Disease seeks to examine the promising avenue of utilizing niosomal transdermal drug delivery systems for the treatment of LSD. This review critically analyzes the current understanding of LSD, explores the limitations of conventional treatment approachesand discusses the potential benefits and challenges associated with niosomal transdermal drug delivery in combating this disease.